'A new god will walk': Shakespeare, the Renaissance, and the birth of the posthuman in Westworld. Issue 1 (November 2019) - Burzyńska, Katarzyna
Westworld, a highly acclaimed TV series by HBO, can boast a whole wealth of references to canonical texts, famous works of art and cultural icons. I would argue that the series alludes to numerous Renaissance works in order to address the crises of humanity in the digital age. The aim of this article is to investigate the parallels between the 'brave new world' of the early modern period and the postmodern period, both from which the series draws inspiration. I wish to discuss the functions of Shakespearean and other early modern references in the context of a dystopian vision of the fall of man and the emergence of a new race.